Advances in Crowdfunding 2020
DOI: 10.1007/978-3-030-46309-0_3
|View full text |Cite
|
Sign up to set email alerts
|

The Global Status of the Crowdfunding Industry

Abstract: The chapter presents key international trends relating to crowdfunding market development, and also provides insights into the current research available attempting to explain such developments. Facts and figures from leading national and regional markets are presented in a comparative manner, with specific focus on the diversity of crowdfunding models, growth trajectories, and geographical variations. The chapter shows that crowdfunding is no longer a fringe activity but gradually moving mainstream with subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Another research by Baber (2020b) found that integrating FinTech, particularly crowdfunding, into the Islamic banking system will escalate the business cycle of social entrepreneurship and micro-finance and build a firm platform for the global Islamic philanthropy system. Global crowdfunding is growing at 44%, with total assets of USD 290 billion to USD 418 billion from 2016 to 2017, respectively (Ziegler et al, 2020). Despite this unprecedented growth, the crowdfunding market is also subject to some limitations especially within the framework of Islamic jurisprudence.…”
Section: Author's Suggestionmentioning
confidence: 99%
“…Another research by Baber (2020b) found that integrating FinTech, particularly crowdfunding, into the Islamic banking system will escalate the business cycle of social entrepreneurship and micro-finance and build a firm platform for the global Islamic philanthropy system. Global crowdfunding is growing at 44%, with total assets of USD 290 billion to USD 418 billion from 2016 to 2017, respectively (Ziegler et al, 2020). Despite this unprecedented growth, the crowdfunding market is also subject to some limitations especially within the framework of Islamic jurisprudence.…”
Section: Author's Suggestionmentioning
confidence: 99%
“…Ziegler et al [23] also point out that the crowdfunding industry in developed settings has recorded astronomical growth rates since its inception. This observation could be linked to a wider digitisation context, whose enhancement is being pursued by the respective ecommerce and digital competitiveness policies and frameworks [24].…”
Section: Crowdfunding In the Context Of The Developed Nationsmentioning
confidence: 99%
“…The growth rate of the crowdfunding industry in more industrialised countries is nothing short of astonishing, which has been the interest of various researchers and chronicled by [23], amongst others. The increase in crowdfunding has been facilitated by the development of the Internet and information technologies which have enabled startups the financing of their entrepreneurial projects [30].…”
Section: The Importance Of Crowdfunding Adoption To Nigeria and The W...mentioning
confidence: 99%
“…The total global alternative finance volume has grown from $11.06 billion in 2013 to $418.52 billion in 2017 (Ziegler, Shneor and Zhang, 2020). As a result, the concept of crowdfunding has taken more space and growth substantially.…”
Section: Global Scenario Of Crowdfundingmentioning
confidence: 99%